1998
DOI: 10.1016/s0014-5793(98)01202-2
|View full text |Cite
|
Sign up to set email alerts
|

Conformational analysis of the endogenous μ‐opioid agonist endomorphin‐1 using NMR spectroscopy and molecular modeling

Abstract: Endomorphin-1 (Tyr-Pro-Trp-Phe-NH P ) is a highly selective and potent agonist of the W W-opioid receptor. To identify structural attributes unique to this opioid peptide and potential sites of recognition, a conformational analysis has been performed using multidimensional NMR and molecular modeling techniques. The spectroscopic results, derived from experiments in both DMSO and water, indicate that endomorphin-1 exists in the cis-and trans-configuration with respect to the Pro-omega bond in approximately 25%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
124
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(136 citation statements)
references
References 41 publications
10
124
2
Order By: Relevance
“…The sequence of endomorphins also includes a spacer (Pro), which joins the pharmacophoric residues. Podlogar et al (1998) presented a Pro-opiomelanocortin…”
Section: Structure-activity Relationship Studiesmentioning
confidence: 99%
“…The sequence of endomorphins also includes a spacer (Pro), which joins the pharmacophoric residues. Podlogar et al (1998) presented a Pro-opiomelanocortin…”
Section: Structure-activity Relationship Studiesmentioning
confidence: 99%
“…Nevertheless, other earlier experimental and computational studies carried out on the EM1 and various EM derivatives provided also information about the rotamer states of the side chain of aromatic amino acids. In the case of the trans-isomer of EM1, the data derived from NMR measurements indicated that the side chain of Tyr 1 residue could adopt the trans rotamer; however, based on the results obtained from MD simulations, this side chain was found to be characterized by the g ()) rotamer state (23 4 ]EM2 derivatives pointed out that the side chain of Tyr 1 residue showed a preference for the trans rotamer in the case of cis-isomers, while the g ()) rotamer was detected as the preferred conformation of the side chain of Phe 3 amino acid in the case of both cis-and trans-isomers (13). Moreover, the results of this NMR study indicated that the g(+) rotamer was favored for the side chain of the bMePhe 4 …”
Section: U-w and V Conformational Spacesmentioning
confidence: 97%
“…Other earlier experimental and computational studies also pointed out that various intramolecular H-bonds could be observed for the conformational states of EMs and their derivatives. In the case of the trans-isomer of EM1, during the MD simulation, the Tyr 1 -CO ‹ Phe 4 -NH H-bond appeared, playing a role in the structural stabilization of type III b-turn; furthermore, an additional H-bond evolved between the Pro 2 -CO and C-terminal NH 2 groups was detected (23). Based on the results of NMR measurement combined with SA calculation, the rS-type open conformer of the trans-isomer of EM2 was found to be stabilized by two intramolecular H-bonds, such as the Tyr Aromatic-aromatic and proline-aromatic interactions In the case of peptides, not only the intramolecular H-bonds but other interactions (e.g., aromatic-aromatic and proline-aromatic interplays) also play a relevant role in the determination and stabilization of their 3D structure.…”
Section: Intramolecular H-bondsmentioning
confidence: 99%
“…Hence endomorphins contain Pro in position 2, they exist as an equilibrium mixture of cis-and trans-conformations [48] Consequently, the bioactive conformations of endomorphins remained an unanswered question. However, a slightly bent backbone structure was proposed for receptor-bound ligands, more recently four structural parameters were confirmed for high µ-opioid activity.…”
Section: Structural Modifications Of Endomorphinsmentioning
confidence: 99%